(untitled) (Contemporary Society and Politics Journal, 2024)
This research stems from the fact of weak Islamic insights among the community in Pulau Tengah, Kerinci, and simultaneously observes the crucial role of Buya (religious leaders) in addressing this issue. The aim of this study is to understand the formation and utilization of Buya’s authority in strengthening the community’s Islamic insights through a network of study groups. The research method used is qualitative with a descriptive approach. Data collection in this study employed observation, interviews, and documentation methods. The results show that the form of authority possessed by Buya that attracts people to learn about religious knowledge is partly due to their charisma and demeanor. In Pulau Tengah village, there are five study group networks: Riyadhus Shalihin led by Buya Sumarlin, Miftahul Jannah led by Buya Muksin, Uswatul led by Buya Hudri Hamzah, Qowaidul Iman led by Buya Sabbanuddin, and Biyadatul Hidayah led by Buya Ronaldi Asy’ari. Generally, these Buya do not have traditional or legal authority but rely on charismatic authority in carrying out their preaching activities.